STUDY ON PALM OIL LEAF STEM AS BIOMASS FUEL FOR YTP-UNIB-2013 DRYER - Wahyudi Febrianto Putra; Yuwana Yuwana; Bosman Sidebang (Jurnal Agroindustri, 2014)
Purpose of this research was to determine the relation between fuel supply and temperature in the drying chamber of YTP-UNIB-2013 Biomass Dryer; and to describe performance of the dryer operated using palm oil leaf stem as the biomass fuel.  The stems were cleaned out of  leaves, cut into 5-7 cm in length, dried so that their water content less then 10%.Temperature and humidity were recorded every 15 minutes p to 3 hours of burning. In order to maintain maximal temperature in the drying chamber, biomass fuel was added at the time the temperature start decreasing. The time for the additional sample to be burned was recorded.  Each of burning sample process was repeated three time to have accurate data. Result of regression analysis showed that drying chamber temperatures (T) were related to the amount of palm oil stems as biomass fuel by following an equation of T = 12.013Q + 16.293 with coefficient of determinant R² = 0.8706.  Performance tests of the Biomass Dryer indicated that by using 4.4 kg/hour of palm oil stem as biomass fuel, average temperature of the chamber dryer was 65°C and capable of evaporating clear water up to 2,548 kg/hour. Therefore it could be concluded that in general, workability of the YTP-UNIB-2013 Biomass Dryer by using palm oil leaf stem as the biomass fuel was effective.